Studi Pengalaman Pengguna pada Aplikasi Telemedicine Halodoc: Temuan dan Rekomendasi - Wenripin Chandra; Mirza Ilhami; Ariwibowo, Suminar; Riche, Riche; Napitupulu, Segar (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
Telemedicine is an online medical service that allows users to receive treatment or health consultations without needing to visit healthcare facilities in person. One of the popular platforms providing this service is Halodoc. On this platform, users can consult with doctors via chat, make hospital appointments with partner facilities, purchase medications, check lab results, and receive health updates. This study aims to evaluate the user experience of the Halodoc application using the User Experience Questionnaire (UEQ) method. Data collection was conducted through a questionnaire distributed via Google Forms to facilitate participation. A total of 200 participants were involved in this study. The evaluation was based on six UEQ dimensions: Attractiveness, Efficiency, Perspicuity, Dependability, Stimulation, and Novelty. The evaluation results show that the Halodoc application received a score of -1.04 on the Attractiveness dimension (negative), 1.29 on Efficiency (positive), 0.28 on Perspicuity (positive), -1.10 on Dependability (negative), 1.51 on Stimulation (positive), and 0.92 on Novelty (positive). Based on these results, it can be concluded that overall, Halodoc provides a